PENGEMBANGAN LEMBAR PENILAIAN UNTUK MENGUKUR TINGKAT LITERASI ILMIAH SISWA DI ERA REVOLUSI 4.0 - Syarifah Rita Zahara; Riska Imanda; Sirry Alvina (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop an assessment sheet as a measuring tool for the level of scientific literacy in the 4.0 revolution era for high school students in North Aceh. The development model used in this study is the ADDIE model which consists of 5 steps, namely: analysis, design, development, implementation, and evaluation. Samples were selected by stratified cluster random sampling and purposive sampling. The instruments used were in the form of a module quality assessment sheet filled out by expert validators and a questionnaire response sheet for teachers and students. The data analysis used is the percentage formula. The average percentage of module quality assessment questionnaire sheets obtained from 6 validators is 93.00% while the responses of teachers and students are 84.65; 83.81%. The results of the research can be concluded that the assessment sheet as a measuring tool for the level of scientific literacy in the 4.0 revolution era for high school students throughout North Aceh which has been developed is suitable for use in chemistry learning and it is hoped that there will be further research for other materials in a wider scope